ANALYSIS OF THE STRUCTURE OF PLANNING OF K.H. MUHAMMAD MACHDOR UNIVERSITY OF MUHAMMADIYAH CIREBON (UMC) CONCRETE STRUCTURES USING SNI 2013 - Ricki Saputra; Sumarman Sumarman (Journal of Green Science and Technology, 2017)
Planning structure can be defined as a mix betweenart and science combined with intuition expert structure of the behavior of the structure with the basic knowledge in statics, dynamics, mechanics of material, and analysis, to produce a structure economical and safe, during services. (Agus Setiawan , 2008). Over time and the times in Indonesia humans can innovate to design buildings with some more modern building style. In addition in designing a building structure, we need a few materials that can be used as an ingredient implementation.Structural material that can be used includes wood, bamboo, concrete, steel, or any other supporting material. As well as on building construction projects K.H. Muhammad Machdor Universitas Muhammadiyah Cirebon Campus 2 by using concrete construction. Planning the contruction of its own building structure refers to the regulation SNI 1727-2013 and Pedoman Perencanaan Pembebanan Untuk Rumah dan Gedung 1987regarding the impositionÂ  and use of seismic regulations stipulated in SNI 1726-2012. The preparation and the planning itself is assisted using modelingExtended Three Dimension Analisys of Building System ETABS v.9.5.0.